Reindeer husbandry under global change in the tundra region of Northern Fennoscandia - Käyhkö Jukka; Horstkotte Tim; Aikio Antti; Forbes Bruce; Jepsen Jane; Johansen Bernt; Kivinen Sonja; Oksanen Lauri; Olofsson Johan; Utsi Tove; Vehmas Jarmo (University of Turku, 2022)
The Nordic Centre of Excellence (NCoE) TUNDRA (“How to preserve the tundra in a changing climate”) has been a 5-year project (2011–15) within the Top-Level Research Initiative (TRI) by NordForsk. This report combines the key results and a synthesis of the NCoE TUNDRA with earlier research to provide a comprehensive picture of the interplay between the tundra ecosystem, climate change and reindeer husbandry to relevant stakeholders.
Most recent climate projections suggest that by the 2070s, temperature conditions that are warm enough for tree growth (> 10 °C average temperature during summer months) will cover almost all of northern Fennoscandia, excluding only the highest-altitude areas of the Scandinavian mountains. A warming climate will promote growth of shrubs and trees, a process that decreases the area of the tundra biome remarkably. The projected increase in spring temperatures will enhance snow melting. Together with the expansion and densification of shrub vegetation, this can significantly decrease surface reflectance (albedo), and have an amplifying feedback on global climate warming. Therefore, hindering shrub expansion and preserving the circumpolar high albedo tundra biome would serve as climate change mitigation.
Herbivores (animals feeding on plants) have a strong impact on vegetation communities. The most important herbivores in Northern Fennoscandia include large mammals (reindeer), small mammals (rodents), and insects (geometrid moths). Their exact effect, however, varies between the animal groups and their population dynamics, seasons, weather conditions, and vegetation communities, and is dependent also on the combined impact of these animal groups. Reindeer grazing in particular has the potential to counter-impact the climate-induced shrubification. The maximum grazing impact on woody plants is obtained if reindeer are present in a region during early growing season in June and early July. In addition, grazing has an impact on plant biodiversity. By preventing the invasion of trees, tall shrubs and forbs, reindeer maintain the openness of the tundra, which is a precondition for the survival of many small-sized arctic plant species. Although grazing may disturb also these plant species, the net impact of intense summer grazing can be positive at the population level.
From a transdisciplinary perspective, tundra is not only a biome, but also a social-ecological system (SES) incorporating humans and their activities, including reindeer husbandry. Decision-making involves various aspects of this complex social-ecological system and is, therefore, always a compromise and a matter of values and opinions. Reindeer husbandry exhibits major legal and administrative differences in local, regional, and state governance between Finland, Norway and Sweden. Anticipated changes in climate and within the societies require reindeer husbandry to adapt to these transformations. Future is not pre-determined but unveils itself as a chain of decisions and actions. Therefore, various scenarios of the future of the social-ecological system in Northern Fennoscandia – including reindeer husbandry – can be foresighted depending on the circumstances, decisions and actions.
Current tensions between stakeholders – including reindeer herders, other land users, Sámi and non-Sámi individuals, and the governance system – stem from different values regarding ecological, cultural, social, and economic matters. These tensions may inhibit fruitful discussion and feasible decisions, and may lead to a future that is undesirable for many, if not all parties. At present, there is too little interaction, and inadequate, unequal discussion between the stakeholders. From the herders’ perspective, unclear legislation and lack of self-determination are considered as threats for the livelihood. To improve the quality of decision making, planning and actions regarding future land use and livelihoods should be co-designed by different stakeholders. To overcome the historical apprehension between the parties, a neutral boundary organisation might serve as an appreciated mediator.